Adab Guru Menurut Imam Nawawi dalam Buku Adabul Alim Wal Muta’allim dan Relevansinya dengan Kode Etik Guru di Indonesia - Nasrul HS; Eka Septi Wulan Sari Siregar (Instructional Development Journal, 2022)
Abstract: Education is teaching and learning process conducted by students and teachers. Teachers have a very important role in education in schools.  This research aimed at knowing Teacher’s Ethics according to Imam Nawawi in the book Adabul Alim Muta’allim and its relevance to Indonesian teacher's ethics code.  It was a library research.  Documentation technique was used for collecting the data.  Content analysis technique related to the content containing in the book Adabul Alim Muta’allim and Indonesian teacher's ethics code was used for analyzing the data.  The findings in this research showed that Imam Nawawi's ethical theory generally comes from the Al-Qur'an and As-Sunnah.  In general, his theory has relevance to the Indonesian teacher’s ethics code.  According to Imam Nawawi, teacher ethics have similarities with the Indonesian teacher’s ethics code, including: teacher’s ethics in teaching, teacher’s ethics to persons, teacher’s ethics to students, teacher’s ethics to science and to others.Abstrak: Pendidikan adalah proses belajar mengajar yang dilakukan oleh siswa dan guru. Guru memiliki peran yang sangat penting dalam pendidikan di sekolah. Penelitian ini bertujuan untuk mengetahui Etika Guru menurut Imam Nawawi dalam kitab Adabul Alim Muta’allim dan relevansinya dengan kode etik guru Indonesia. Itu adalah penelitian kepustakaan. Teknik dokumentasi digunakan untuk mengumpulkan data. Teknik analisis isi yang berkaitan dengan isi yang terdapat dalam kitab Adabul Alim Muta’allim dan Kode Etik Guru Bahasa Indonesia digunakan untuk menganalisis data. Temuan dalam penelitian ini menunjukkan bahwa teori etika Imam Nawawi pada umumnya bersumber dari Al-Qur'an dan As-Sunnah. Secara umum, teorinya memiliki relevansi dengan kode etik guru Indonesia. Menurut Imam Nawawi, etika guru memiliki kesamaan dengan kode etik guru Indonesia, antara lain: etika guru dalam mengajar, etika guru terhadap orang, etika guru terhadap siswa, etika guru terhadap ilmu pengetahuan dan lain-lain.  TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//   This page is in Indonesian Translate to English    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate Indonesian to EnglishPRO Never translate Indonesian Never translate ejournal.uin-suska.ac.id